PRACTICAL TRAINING METHODS IN economic HIGHER schools - T. Godina; A. Terekhova (Вестник университета)
The article describes the essence of one of the practical teaching methods - the personal-active approach. Providing detailed description of the personal-active approach authors bring forward the need for increasing attention to the practical side of educational process in economic universities and other higher schools- getting skills required in future professional areas.